Profit and Capacity Analysis of Beef Cattle Business; Case Study - Tiwow, Herman Adrian; Osak, Richard E.M.F.; Tumewu, Judi M.; Patonengan, Al Riski (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2025)
This study aims to analyze the profitability and carryingcapacity of a beef cattle farm in Mapanget Village, Talawaan District,North Minahasa. The respondent, Mr. Nicolaas Kandowangko, servedas the data source for this study and owned 54 cattle. This studyutilized a survey method through observation and in-depth interviewswith the sample farmers using a prepared questionnaire. The analysismethod used the profit analysis formula π = TR – TC, where π was thefarmer's profit (IDR/period), TR (Total Revenue) the value of revenueobtained from sales, and TC (Total Cost) the total costs incurred,consisting of fixed costs and variable costs. The study concluded thatMr. Nicolaas Kandowangko's beef cattle farm generated a profit of94,075,333 IDR. The research demonstrated that profitabilitydetermination of a beef cattle business was not only based on total salesrevenue but also on the capacity to meet the livestock's feed needs.Production costs per period were also taken into account. The R/Cratio Mr. Nicholas beef cattle business result showed that the businesswas worthy of further development.